Dear Martin - Stone, Nic (Crown, 2017)
Writing letters to the late Dr. Martin Luther King Jr., seventeen-year-old college-bound Justyce McAllister struggles to face the reality of race relations today and how they are shaping him
Keywords: King, Martin Luther; Race relations; Racism; Racial profiling in law enforcement; Police brutality; African Americans; Letters; Jugendbuch